Ultrasensitive interferons quantification reveals different cytokine profile secretion in inflammatory myopathies and can serve as biomarkers of activity in dermatomyositis - Bolko, Loïs; Anquetil, Céline; Llibre, Alba; Maillard, Solène; Amelin, Damien; Dorgham, Karim; Bondet, Vincent; Landon-Cardinal, Océane; Toquet, Ségolène; Mariampillai, Kuberaka; Malatre, Samuel; Mahoudeau, Alexandrine; et al. (Frontiers in Immunology, 2025)
ObjectiveThe objective of this study was to evaluate the presence of different types of interferon in idiopathic inflammatory myopathies (IIM) and their subgroups using ultrasensitive cytokine detection techniques (SIMOA) and to assess their potential as activity biomarkers.MethodsDisease activity was measured at the time of serum collection and assessed by manual muscle testing eight (MMT8 score 0-150), muscle enzymes to calculate the Physician Global Assessment (PGA) (0-10). Patients were classified as active if PGA>5.Serum IFN-α and IFN-γ levels was measured using the single molecule array (SIMOA) technique. Serum IFN-β level was measured by Elisa. Correlation between IFN levels and disease activity were performed.ResultsWe included 242 IIM patients and found a good correlation between type I Interferon (IFN) and dermatomyositis disease activity. IFN-α and IFN-β was highly correlated with disease activity (r=0.76 and r=0,58). To evaluate whether the different types of Interferons could serve as biomarkers of activity, we generated ROC curves. Patients with active DM had a higher median IFN-α level (0.49 pg/ml [0.1-3.7]) compared with non-active patients (0.03 pg/ml [0.01-0.07] p<0.05). The area under the curve was 0.90 IC95 (0.76-0.97) p<0.05. Furthermore, Myositis-specific antibodies appear to be associated with a different secretion profile; patients with anti-MDA 5 antibodies had higher level of IFN-α than most other antibodies (6.58 vs 0.14 p<0.005). NXP2 had higher IFN-β level than patients with Tif1γ antibodies.ConclusionSerum IFN-α level measured by SIMOA is a reliable biomarker of DM activity. Myositis-specific antibodies appear to be associated with a different secretion profile. This data needs to be confirmed in order to select the good therapeutics strategies in DM.